Differences the Effectiveness of Using Conventional Toothbrush and Modified Toothbrush Handle (SIGIGA) in Reducing Debris Index With Children in Down Syndrome - Stefani Dwi Adelia Putri Susanto; Isnanto; Bambang Hadi Sugito; Sunomo Hadi (International Journal of Advanced Health Science and Technology, 2024)
Down syndrome children are mentally retarded and most of them have poor oral health and are unable to carry out dental hygiene independently due to cognitive and motor limitations. It was found that 83% of dental hygiene (debris index) was in the moderate category in children with Down syndrome. Efforts to improve dental hygiene can be done by using a modified toothbrush. The aim of the research is to determine the difference in the effectiveness of using a conventional toothbrush and a modified toothbrush with a handle (SIGIGA) in reducing the debris index in children with Down syndrome. This type of research is quasi-experimental. The sample size was 30 respondents from children with Down syndrome who were selected using a total sampling technique. The data collection instrument used was the debris index examination sheet. The data analysis techniques used are the Wilcoxon test and the Mann-Whitney test. The results of the Wilcoxon test to see the difference in plaque scores before and after treatment obtained significant results ρ (0.001) < 0.05 in the conventional toothbrush group and the modified handled toothbrush group. The results of the Mann-Whitney test showed ρ (0.000) < 0.05. This value shows that H0 is rejected, so there is a difference in the effectiveness of using a conventional toothbrush and a modified toothbrush with a handle (SIGIGA) in reducing the debris index in children with Down syndrome. Conclusions from the research : There is a difference in the effectiveness of using a conventional toothbrush and a modified toothbrush with a handle (SIGIGA) in reducing the debris index in children with Down syndrome.